2022
DOI: 10.3389/fcimb.2022.804611
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Rapid Multiplex PCR on Antimicrobial Therapy Guidance for Ventilated Hospital-Acquired Pneumonia in Critically Ill Patients, A Prospective Observational Clinical and Economic Study

Abstract: ObjectivesTo investigate the potential impact of the syndromic multiplex FilmArray® Pneumonia plus Panel (FAPP) on the antimicrobial treatment guidance of patients with ventilated hospital-acquired pneumonia (VHAP).MethodsRespiratory fluids from 100 adult patients with VHAP, receiving invasive mechanical ventilation in three intensive care units from one French university hospital, were tested prospectively using FAPP. Conventional cultures were performed in parallel as routine practice. Clinicians were left b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Nucleic acid amplification methods, such as multiplexed polymerase chain reaction (PCR), have shown high diagnostic efficacy [11] and can reduce the time to detect some antibiotic resistance mechanisms [12,13]. These methods can optimize the initial antibiotic treatment, reducing broad-spectrum antibiotic use and associated risks [14,15]. However, they have limitations, such as false negatives and positives.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleic acid amplification methods, such as multiplexed polymerase chain reaction (PCR), have shown high diagnostic efficacy [11] and can reduce the time to detect some antibiotic resistance mechanisms [12,13]. These methods can optimize the initial antibiotic treatment, reducing broad-spectrum antibiotic use and associated risks [14,15]. However, they have limitations, such as false negatives and positives.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies simulated the impact of m-PCR results by comparing the antibiotics prescribed in practice by clinicians unaware of the m-PCR results to those chosen in theory by experts informed of the m-PCR results. The anticipated proportion of antibiotic de-escalation when using m-PCR was around 40% in the literature [16,21,[28][29][30]. For instance, Guillotin et al showed only 37% of predicted broad-spectrum antibiotic therapies when using m-PCR compared with 88% when following clinical guidelines [28].…”
Section: Discussionmentioning
confidence: 99%
“…The anticipated proportion of antibiotic de-escalation when using m-PCR was around 40% in the literature [16,21,[28][29][30]. For instance, Guillotin et al showed only 37% of predicted broad-spectrum antibiotic therapies when using m-PCR compared with 88% when following clinical guidelines [28]. Buchan et al reported a potential de-escalation or discontinuation of antibiotic therapy based on m-PCR results in 48% of patients, resulting in an average saving of 6.2 antibiotic days/patient.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from that study demonstrated potential cost-savings with the mPCR test bundle, primarily due to no longer needing to perform certain standard of care tests, such as singleplex nasal PCRs or urinary antigen testing. Furthermore, in a prospective study of VAP patients that received mPCR, Guillotin et al demonstrated that the cost to prevent one day of non-optimized antibiotics with mPCR was more expensive but more effective than relying on antimicrobial therapy recommendations alone [41]. This evidence points toward the value of mPCR in enhancing patient care while potentially streamlining healthcare expenditures.…”
Section: Cost Considerationsmentioning
confidence: 99%